ANALISIS MANAJEMEN STRATEJIK PADA “RESTORAN MENU KOREA - Lavenia Permata Sari; Ahmad Setiawan Nuraya; Zaid Muhammad Zaidan; Rudi Samuel Parlindungan (Yayasan Nuraini Ibrahim Mandiri, 2024)
Analisis visi dan misi